Subacute Sensory Ataxic Neuronopathy With Thymoma Presenting Marked Improvement After Steroid Therapy - Nishijima, Haruo; Onodera, Ken; Sato, Nobuyuki; Ueno, Tatsuya; Hikichi, Hiroki; Haga, Rie; Arai, Akira; Suzuki, Chieko; Nunomura, Jin-ichi; Baba, Masayuki; Tomiyama, Masahiko (Frontiers in Neurology, 2019)
Subacute sensory ataxic neuronopathy is a well-known form of paraneoplastic syndrome. Most sensory neuronopathies are associated with small cell lung cancer and anti-Hu antibodies, and usually show only slight improvement with immunotherapy. To date, there have been few reports of neuropathy associated with thymoma and no treatment strategy has been established for thymoma-related neuropathy. Here, we provide the first report of a case of sensory ataxic neuronopathy with thymoma that showed marked improvement after steroid therapy, even though preceding intravenous immunoglobulin treatments and tumor resection were less effective. A 57-year-old Japanese man was referred to our hospital with a 6-week history of distal paresthesia in his four limbs and an unsteady gait. He presented with left-dominant ataxia in his four limbs due to reduced sensation in his extremities. He also complained of constipation, difficulty urinating, and erectile dysfunction. Upon investigation, including electrodiagnostic studies, the patient was diagnosed as having sensory ataxic neuronopathy with invasive thymoma. A first round of intravenous immunoglobulin therapy, a following thymectomy, and a second round of intravenous immunoglobulin therapy after the surgery were not effective in treating his neurological symptoms. Subsequently, oral steroid therapy was started, which brought about a remarkable improvement; 6 weeks after the beginning of the steroid therapy, his neurological symptoms were resolved, except for slight distal paresthesia in his feet. Although rarely reported, thymoma can underlie sensory neuronopathy, and the response of thymoma-associated sensory neuronopathy to immunotherapy might be better than that of anti-Hu antibody-related neuropathies. Even if the first immunotherapy is not effective in treating neuropathy with thymoma, further immunomodulatory treatment should be tried after treating the tumor.